2012
DOI: 10.1186/1471-2407-12-371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgen deprivation on brain function in prostate cancer patients – a prospective observational cohort analysis

Abstract: BackgroundDespite a lack of consensus regarding effectiveness, androgen deprivation therapy (ADT) is a common treatment for non-metastatic, low-risk prostate cancer. To examine a particular clinical concern regarding the possible impact of ADT on cognition, the current study combined neuropsychological testing with functional magnetic resonance imaging (fMRI) to assess both brain activation during cognitive performance as well as the integrity of brain connectivity.MethodsIn a prospective observational cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 45 publications
8
77
2
1
Order By: Relevance
“…Chao and colleagues (2012) reported decreased medial prefrontal cortical activation during a working memory task, as well as decreased connectivity between the medial prefrontal cortex and other regions in men on ADT compared to controls. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Chao and colleagues (2012) reported decreased medial prefrontal cortical activation during a working memory task, as well as decreased connectivity between the medial prefrontal cortex and other regions in men on ADT compared to controls. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Although most cancer diagnoses originate outside the central nervous system (CNS), cognitive decline affects an estimated 19-78% of these patients (Wefel and Schagen, 2012). Neuroimaging studies suggest that this cognitive impairment stems from subtle but diffuse brain injury (Chao, et al, 2012; D'Agata, et al, 2013; Hsieh, et al, 2014; Koppelmans, et al, 2014) [see reviews by: (de Ruiter and Schagen, 2013; McDonald and Saykin, 2013; Scherling and Smith, 2013)].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these changes were positively correlated with changes in executive function in the aerobic training group, but the stretching/balance group also showed alterations in functional connectivity, possibly representing experience-dependent plasticity (Voss et al 2010). These findings may be relevant to men with PCa treated with ADT as there is some evidence from a study of 30 PCa survivors (median age 68 years), which found that 6 months of ADT was associated with decreased grey matter volume, reduced brain functional connectivity and reduced neural activations during cognitive control tasks (Chao et al 2012(Chao et al , 2013. Collectively, the current evidence indicate that regular exercise training can offer protective benefits to cognitive function in healthy older adults, but in men with PCa receiving ADT, the direct link between exercise and cognitive function has not been established.…”
Section: :4mentioning
confidence: 71%
“…Furthermore, the use of ADT has been associated with an almost two-fold increased risk for developing Alzheimer's disease (AD), with the risk increasing with treatment duration (Nead et al 2016). Thirteen prospective studies have objectively assessed cognitive function in patients receiving ADT (Table 1) (Green et al 2002, Cherrier et al 2003, 2009, Salminen et al 2003, Almeida et al 2004, Alibhai et al 2010, Matousek & Sherwin 2010, Mohile et al 2010, Chao et al 2012, Tan et al 2013, Gonzalez et al 2015. Five of these studies reported no effect (Almeida et al 2004, Matousek & Sherwin 2010, Mohile et al 2010, Chao et al 2012, Tan et al 2013, which is likely related in part to methodological differences in participant characteristics, study design and analyses.…”
Section: The Effects Of Androgen Deprivation On Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation